Cardiac aspects of DiGeorge syndrome: a report of two cases with molecular analysis (Journal of Health Sciences, 2014)
DiGeorge syndrome (DGS) which is also known as velocardiofacial syndrome is caused by a submicroscopic chromosome deletion of band 22q11. It is associated with a disturbed development of the pharyngeal arches. In this report we describe two unrelated male children with clinical features consistent with 22q11.2 microdeletion syndrome characterized by cardiac defect, recurrent respiratory infections and developmental deficiency. Definitive diagnosis is made by Fluorescence In Situ Hybridization analysis (FISH). Children underwent surgical correction of congenital heart defects. During surgery thymic aplasia was confirmed in both children, postoperative course proceeded without major complications. Our report suggests that the criteria in searching for microdeletion 22q11.2 should be expanded and applied in patients with conotruncal and non-conotruncal congenital heart defects and at least one typical feature of this syndrome.